RISK FACTORS OF NEURAL TUBE DEFECTS IN NEONATAL CARE UNIT AT MATERNITY HOSPITAL IN ERBIL GOVERNORATE - Dr. Hasan Mohsin Sulaiman; Dr. Munther Saleh Abed; Dr. Nihad Tariq Farage; Dr. Ali Qais Abdulkafi (Web of Journals Publishing, 2025)
Fetal and newborn mortality are causes of concern when it comes to neural tube abnormalities. The exact cause of neural tube abnormalities is still not fully understood; however, it involves both hereditary and environmental variables. Antenatal diagnosis, multivitamin supplementation, and folic acid supplementation have all contributed to a drop in the prevalence of neural tube abnormalities in the past 30 years, yet some of the decrease remains unexplained.
Keywords: Erbil, risk factors, neural tube abnormalities newborn.